(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Obesity remains a global public health challenge, with bariatric surgery (BS) emerging as an effective intervention for morbid obesity when conservative treatments fail. BS procedures like Roux-en-Y Gastric Bypass (RYGB) and Laparoscopic Sleeve Gastrectomy (LSG) not only facilitate substantial weight loss but also alter the gastrointestinal (GI) tract’s anatomy and physiology, influencing the composition of the gut microbiota. The gut microbiota plays an important role in host metabolism, energy regulation, and nutrient absorption, and its dysbiosis has been linked to obesity and related comorbidities. This review examines the impact of BS on gut microbiota and explores the role of probiotics in postoperative outcomes. Several randomized controlled trials have demonstrated that probiotics can improve GI function by reducing symptoms like bloating, gas, and abdominal pain. They also enhance metabolic profiles by significantly reducing fasting blood sugar, HbA1C levels, and inflammatory markers like TNF-α. Additionally, probiotics have been associated with increased levels of essential nutrients such as vitamin B12 and vitamin D, vital for postoperative recovery. Some studies suggest that probiotics may contribute to weight loss and reductions in waist circumference, especially when combined with weight loss programs and cognitive behavioral therapy. They may also positively influence plasma metabolites and markers related to nonalcoholic fatty liver disease (NAFLD). However, the effects of probiotics on body mass index (BMI), percentage of excess weight loss (%EWL), and the development of small intestine bacterial overgrowth (SIBO) remain inconclusive. The benefits observed in metabolic and nutritional parameters do not always persist after the cessation of probiotic supplementation, highlighting the need for continuous intervention and further research.